Localization genes controlling traits related to flag-leaf and peduncle in durum wheat - Roghayeh Naseri; Kianoosh Cheghamirza; Leila Zarei; Reza Mohammadi; Ali Beheshti Aleagha (بیوتکنولوژی و بیوشیمی غلات, 2023)
Introduction: Among cereals, durum wheat (Triticum turgidum L. var. durum) is one of the most important protein and energy sources after bread wheat. It has a significant role in human nutrition in most countries. Materials and methods: In this study, in order to identify and localization of QTLs controlling traits related to flag leaf and peduncle, 118 durum wheat recombinant inbred lines obtained from the cross between the local genotype of Iran-249 originated from the west of Iran and the local cultivar of Zardak from Kermanshah were evaluated in three environments under rainfall conditions using randomized complete block design along with parents in three replications. QTL analysis for each trait was performed using the inclusive composite interval mapping method to identify genomic regions that significantly affected the studied traits. Results: Based on the analysis of variance, the effect of genotype (recombinant inbred line) was significant in terms of traits related to flag leaf and peduncle in three environments, which indicates the existence of appropriate levels of genetic diversity in the studied population for measured traits. The results of QTL analysis using the inclusive composite interval mapping method led to the identification of 33 QTL for the measured traits. The common and stable QTLs were located in at least two environments on chromosomes 1A, 1B.1, 2B.1 and 5A for peduncle length and diameter traits and on chromosomes 2A, 5A and 7A for flag leaf length, flag leaf width and flag leaf area. Identification of repeatable QTLs in the different environments can indicate the existence of stable genomic regions related to flag leaf and peduncle. On the other hand, a positive and significant correlation was observed between the traits, probably due to the linkage or pleiotropic effect of their controlling QTLs. Also, based on QTL analysis using the two-locus method, the additive main effect, as well as the interaction effect of the QTL× environment, was significant for all traits except for the middle and bottom peduncle diameter. In total, six gene loci with significant additive× additive epistasis effects were identified for the flag leaf area-related traits and top peduncle diameter. Conclusion: Identification and localization of stable QTLs in different environments for some traits related to flag leaf and peduncle can assist in understanding better the genetic basis of these traits to be used in breeding programs, especially in MAS projects.